Impact of Mangrove Damage in Jailolo District, West Halmahera Regency - Samad, Foniike; Dadi, Zakeus (Pattimura University Ambon Maluku Indonesia, 2022)
Jailolo has mangrove plants located on the coast that can protect the coastline from erosion, waves and sea water, but several villages in Jailolo Sub-district have shifted the development of mangrove plants where mangroves have been used as fuel and building materials. Saria Village and Gamtala Village are villages located near the coast and some of the people utilize mangroves as firewood and building materials. Based on the above background, the following problems can be formulated, namely how is the impact of mangrove damage in Jailolo District, West Halmahera Regency? And how to formulate a strategy for handling the impact of mangrove damage in Jailolo District, West Halmahera Regency? This research was conducted in Saria Village and Gamtala Village, Jailolo District, West Halmahera Regency. And the implementation of research in September - October 2021. The number of respondents taken in this study was 60 people consisting of 30 people per village close to the mangrove area. Data analysis techniques used in this research are Internal Factor Evaluation Matrix (IFE), External Factor Evaluation Matrix (EFE), Internal External Matrix (IE), SWOT Analysis Matrix and QSP Matrix (QSPM). The results showed that the impact of mangrove damage in Jailolo District, West Halmahera Regency, the impact on people's lives and the environment that occurred in Saria Village and Gamtala Village was a decrease in the catch of fishermen in this case fish, due to loss of habitat and fish populations, loss of fish breeding ground, causing coastal abrasion, because there is no barrier when the waves or tides due to mangove reduction, can cause sunami because it does not withstand the movement of underwater waves, due to loss of mangrove habitat, SWOT results, with an IFE (Internal Factor Evaluation) value of 2 52 and EFE (External Factor Evaluatin) of 2.50.